Chemical composition and source apportionment of size fractionated particulate matter in Cleveland, Ohio, USA. (November 2016) - Kim, Yong Ho; Krantz, Q. Todd; McGee, John; Kovalcik, Kasey D.; Duvall, Rachelle M.; Willis, Robert D.; Kamal, Ali S.; Landis, Matthew S.; Norris, Gary A.; Gilmour, M. Ian
Abstract: The Cleveland airshed comprises a complex mixture of industrial source emissions that contribute to periods of non-attainment for fine particulate matter (PM2.5 ) and are associated with increased adverse health outcomes in the exposed population. Specific PM sources responsible for health effects however are not fully understood. Size-fractionated PM (coarse, fine, and ultrafine) samples were collected using a ChemVol sampler at an urban site (G.T. Craig (GTC)) and rural site (Chippewa Lake (CLM)) from July 2009 to June 2010, and then chemically analyzed. The resulting speciated PM data were apportioned by EPA positive matrix factorization to identify emission sources for each size fraction and location. For comparisons with the ChemVol results, PM samples were also collected with sequential dichotomous and passive samplers, and evaluated for source contributions to each sampling site. The ChemVol results showed that annual average concentrations of PM, elemental carbon, and inorganic elements in the coarse fraction at GTC were ∼2, ∼7, and ∼3 times higher than those at CLM, respectively, while the smaller size fractions at both sites showed similar annual average concentrations. Seasonal variations of secondary aerosols (e.g., high NO3 − level in winter and high SO4 2− level in summer) were observed at both sites. Source apportionment results demonstrated that the PM samples at GTC and CLM were enriched with local industrial sources (e.g., steel plant and coal-fired power plant) but their contributions were influenced by meteorological conditions and the emission source's operation conditions. Taken together the year-long PM collection and data analysis provides valuable insights into the characteristics and sources of PM impacting the Cleveland airshed in both the urban center and the rural upwind background locations. These data will be used to classify the PM samples for toxicology studies to determine which PM sources, species, and size fractions are of greatest health concern. Graphical abstract: Highlights: PM sources in the Cleveland airshed varied across regions and with seasons. Local industrial source impacts in the urban site were higher than the rural site. Local industrial sources were mostly emitted from steel and coal-fired power plants. Local industrial source impacts were associated with meteorological conditions. Abstract : The Cleveland airshed was enriched with local industrial sources but their contributions were influenced by meteorological conditions and emission source operation conditions.